No Mercy - Richard Pearce; Basaraba, Gary.; George Dzundza; Jeroen Krabbé; Kim Basinger; Terry Kinney; William Atherton; Richard Gere (USA TriStar Pictures, 1986)
Maverick Chicago cop Eddie Jillette poses as a hit man to meet with someone in from New Orleans looking to have a job done. The result is that both the guy and Jillette's partner wind up very dead, while a stunning blonde in on the setup disappears. He heads south to settle the score and soon finds himself being hunted, with the girl in tow and the local police anything but happy. New Orleans may never be the same again.
Maverick Chicago cop Eddie Jillette poses as a hit man to meet with someone in from New Orleans looking to have a job done...
James Carabatsos
Languages : English, German, French, Spanish, Italian Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Swedish, Arabic, Bulgarian, Hebrew
Keywords: Crime; Thriller; Action